Divine Breath and the Process of Creation. The Allusions to Gen 2:7 in the Catechetical Rhetoric of Cyril of Jerusalem - Huovinen, Harri (Vox Patrum, 2024)
Previous scholarship inadequately acknowledged the diverse ways in which Cyril of Jerusalem employed the breath-related vocabulary related to or derived from Gen 2:7. A systematic analysis of Cyril’s catechetical homilies revealed that in his rhetoric, this vocabulary was utilized in several distinct contexts. First, it was used to describe the creation of humans as living beings. Secondly, the vocabulary depicted a pre-Pentecost mediation of the Holy Spirit. Thirdly, the Pentecostal outpouring of the Spirit could be interpreted as another form of “breathing.” Fourthly, breath-related vocabulary was employed in reference to three ecclesiastical rites of initiation, indicating their pneumatological significance. This collective utilization of Biblical accounts of breathing, alongside depictions of post-Biblical ecclesiastical rites, formed a coherent narrative aimed at instructing catechetical audiences about the historical sequence of human creation. This narrative encompassed the divine vivification of the tangible body and postlapsarian revivification through the Holy Spirit. Simultaneously, it became evident that Cyril’s use of this vocabulary aligned with his overall allusionary approach to employing Scripture in catechesis.